The Relationship between Knowledge of Women of Childbearing Age with Interest in Conducting IVA Examinations at the Simarpinggan Health Center, South Tapanuli Angkola District - Riska Maulidanita (Science Midwifery, 2022)
Cervical Cancer is ranked second only to breast cancer which occurs a lot in women. In Indonesia, cervical cancer ranked second in 2020 data sources derived from the Global Burden of Cancer Study (Globocan) from the World Health Organization (WHO) noted, the total cancer cases in Indonesia in 2020 reached 396,914 cases and the total deaths were 234,511 cases. Breast cancer has the highest number of new cases in Indonesia at 65,858 cases or 16.6% of the total 396,914 cancer cases. Cervical (cervical) cancer ranks second with 36,633 cases or 9.2% of total cancer cases. This research is analytical using primary data. The design used in this study was a correlation study using 0.05 chi-square data analysis. Data collection through the distribution of questionnaires with a total sample of 30 respondents at the Simarpinggan Health Center, Angkola District, South Tapanuli.